Future of cardiac resynchronization therapy. (March 2008) - Arujuna, Aruna Vishnu; Ginks, Matthew; Rinaldi, Aldo
Cardiac resynchronization therapy (CRT) has proven to be a beneficial treatment option in patients with severe drug refractory heart failure in the presence of electromechanical dyssynchrony. More recent trials have demonstrated mortality benefits associated with CRT, and even further reductions when combined with an internal cardiac defibrillator. Addressing the 20––30% cohort of patients who do not derive benefit from this novel therapy is a rapidly emerging area of research activity with encouraging results. Here we review the CRT trial evidence that forms the basis of patient-selection guidelines for device implantation and describe the present outstanding issues, alongside identifying future trends in CRT that appear promising.